Causes of late diagnosis of the reproductive organs’ cancer in the opinion of suffering women from urban and rural areas of Lublin as an indicator of the condition of the early cancer detection system: a preliminary report - Domżał-Drzewicka, Renata; Charzyńska-Gula, Marianna; Szadowska-Szlachetka, Zdzisława; Bartoszek, Agnieszka; Stanisławek, Andrzej (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction: Tumours as well as the cardiovascular diseases are the leading causes of deaths in Poland. This article contains excerpts from research on complex causes of late diagnosis of cancer among the region’s residents. Aim of the study: One of the specific aims of the research undertaken was to learn about subjective assessment of women suffering from cancer taking into account its late diagnosis. Material and methods: The research was conducted on 130 women with diagnosed cancer of reproductive organs in the late stage of the disease, who were in oncological care. The method of diagnostic survey in the form of a questionnaire was developed for the study. Results: The research reveals that the place of living has an impact on the opinions of suffering women as for the causes of late diagnosis of cancer and, secondly, that their oncological awareness is low. Conclusions: 1. In the examined group, cancer awareness of women already having cancers – irrespective of the environment of settling, was low and did not constitute the grounds for taking pro-health decisions in the area of the early diagnostic testing of cancer. This fully confirms the need for the research on effective tools to increase the awareness, particularly in the population of healthy persons, including menopausal and postmenopausal women. 2. The opinions indirectly indicate a weaker organization and effectiveness of the activities of the cancer prevention programs in the country than those organized in the city.